Enhancing Critical Thinking Through the Integration of Self-Directed Learning in Sustainable Education in Madrasah - Izzatul Munawwaroh; Dinda Febrianti Putri (Universitas Nurul Jadid, 2024)
This research focuses on improving critical thinking skills through integrating independent learning in the context of continuing education in madrasah. This research explores the effectiveness of a self-directed learning approach in supporting the development of students critical thinking skills and understanding its impact on sustainable educational practices. This research uses a qualitative method with a case study approach, where data is collected through in-depth interviews with teachers and students, observation of the learning process, and analysis of curriculum documents. Research findings show that integrating independent learning significantly improves students’ critical thinking abilities, developing the ability to plan, evaluate, and reflect on their learning independently. Students who engage in independent learning improve analytical skills and creativity in dealing with problems and are better prepared to apply continuing education principles in everyday contexts. The implications of this research emphasize the importance of implementing independent learning in the madrasah curriculum to develop the critical thinking skills needed in continuing education and the challenges that need to be considered in adapting this method to the needs and learning styles of diverse students.